Shariah compliant audit checklist for tourism accommodation premises - Othman, Rashidi; .., Siti Syahirah Saffinee; Hashim, Khairusy Syakirin Has-Yun; Hj. Baharuddin, Zainul Mukrim; Mahamod, Lukman Hakim; Ibrahim, Mansor (2015)
The awareness towards Shariah compliant concept to be implementing in Hotel sector has been discussed since 1982. An extensive literature and research described variety of approaches and methods to improve the understanding of the concept. Specifically in many of the hotel operations, one of the prior parts is to provide comfortable and affordable rooms to guests. It’s related to the hospitality in Islam, which give good services to the guest in term of place to stay. However, even though in Malaysia there are nearly 3000 hotels that contribute to almost 200,000 rooms, only less than 10% are considered Islamic rooms. On top of that, the total number of tourist from Islamic countries to Malaysia has increased steadily and is forecast to contribute 181 billion in 2018. Therefore this paper aimed to develop Shariah compliant Audit Checklist System for Tourism Accomodation Premises in Malaysia which comprises of scorecards and guidelines. This Shariah compliant audit system will be used in the hotel industry to rate the room services whether according to the Shariah elements or not. These elements will be listed through scorecard which will be guided through guidelines. The project will be divided into 2 aspects which are intangible and tangible elements such as operation, facilities, services and product. The significant outcomes from this research will be the new Audit Checklist for Shariah Compliant Hospitality in Malaysia particularly in Muslim World which covers not only the Shariah requirement, but also the tourism industry and safety aspects.